AB1038 Metacarpal Bone Loss in Patients with Rheumatoid Arthritis Estimated by an Automated New Digital X-Ray Radiogrammetry (DXR) Method – Initial Experience. (9th June 2015) - Thodberg, H.H.; Böttcher, J.; Oelzner, P.; Renz, D.M.; Wolf, G.; Pfeil, A.
Abstract : Background: The DXR method measures the cortical bone thickness in the shafts of the metacarpals and has demonstrated its relevance in assessment of hand bone loss in Rheumatoid Arthritis (RA). Objectives: To validate a new implementation of the DXR method in comparison with the original version in RA patients. We examined how many images the old and the new versions accept, we studied the agreement of their measurements of the metacarpal index (MCI), and we correlated the MCIs to the Larsen score and the presence of erosions. Methods: The new implementation is an extension of the BoneXpert method used in pediatrics and differs in two ways from the old DXR method: (1) It adopts a new approach to analyse the images, which automatically validates the result for most images, and (2) it defines the measurement region relative to the ends of the metacarpals. 49 patients with verified RA and average Larsen score 2.6, with SD 1.3. Results: The new version correctly analysed all 49 images, and 45 were automatically validated. The 4 images flagged for visual clearance were all found to be correctly analysed – three had Larsen score 5, and one had score 4. The old version requires visual clearance of all images, and all were found to be correctly analysed. The SD between the MCI results of the two versions was 2.9% of the mean MCI. The correlation of MCI to Larsen score was –0.81 in both versions, and there was no significant difference in their ability to detect erosions. Conclusions: The new DXR implementation validated 92% of the cases automatically, while having the same good correlation to RA severity as the old version. Acknowledgements: HHT is the owner of Visiana, which develops and markets the BoneXpert medical device. Disclosure of Interest: None declared